2018
DOI: 10.1371/journal.pone.0209267
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of executive functions to mathematical learning difficulties and mathematical talent during adolescence

Abstract: Are mathematical learning difficulties caused by impairment of the abilities that underlie mathematical talent? Or are mathematical difficulties and talent qualitatively different? The main goal of this study was to determine whether mathematical learning difficulties are explained by the same executive functions as mathematical talent. We screened a pool of 2,682 first-year high school students and selected 48 for evaluation, dividing them into three groups: those with mathematical learning difficulties (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
1
26
0
3
Order By: Relevance
“…Recent empirical research has largely been focused on associations between mathematical competencies and domain-general abilities. In sum, it has been found that higher competencies are associated with higher information-processing speed (Passolunghi & Lanfranchi, 2012), larger short-term and working memory (Berg & McDonald, 2018; Peng, Namkung, Barnes, & Sun, 2016), higher executive functions (Abreu-Mendoza, Chamorro, Garcia-Barrera, & Matute, 2018; Bull & Lee, 2014), enhanced logical reasoning abilities (Attridge & Inglis, 2013; Morsanyi, Devine, Nobes, & Szucs, 2013), and better visuo-spatial abilities (Benbow & Minor, 1990; Frick, 2018). A review article by Myers, Carey, and Szűcs (2017) showed that these general correlates of mathematical competencies can also be regarded as characteristics of mathematically gifted individuals, even though the authors also noted that the current body of evidence is too limited to draw strong conclusions on this issue.…”
Section: Application Of the Tad Framework To Different Achievement Domentioning
confidence: 99%
“…Recent empirical research has largely been focused on associations between mathematical competencies and domain-general abilities. In sum, it has been found that higher competencies are associated with higher information-processing speed (Passolunghi & Lanfranchi, 2012), larger short-term and working memory (Berg & McDonald, 2018; Peng, Namkung, Barnes, & Sun, 2016), higher executive functions (Abreu-Mendoza, Chamorro, Garcia-Barrera, & Matute, 2018; Bull & Lee, 2014), enhanced logical reasoning abilities (Attridge & Inglis, 2013; Morsanyi, Devine, Nobes, & Szucs, 2013), and better visuo-spatial abilities (Benbow & Minor, 1990; Frick, 2018). A review article by Myers, Carey, and Szűcs (2017) showed that these general correlates of mathematical competencies can also be regarded as characteristics of mathematically gifted individuals, even though the authors also noted that the current body of evidence is too limited to draw strong conclusions on this issue.…”
Section: Application Of the Tad Framework To Different Achievement Domentioning
confidence: 99%
“…Normal, but low, nonverbal intelligence is a frequent finding in children with learning disabilities such as dyslexia and dyscalculia43 and, together with general cognitive resources like executive functions, has been emphasized in recent models of LDs 44. Recently, executive deficits in a large sample of teenagers with mathematical learning difficulties were reported 45. Concerning learning disabilities, according to Johnson (2012), a single specific or modular deficit, such as phonological processing impairment in dyslexia or numerical processing impairment in dyscalculia, may not be enough to characterize the individual’s performance as impaired.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is grounded in empirical evidence. For example, in an investigation of the differences between math talent and math disability, Abreu‐Mendoza et al (2018) found executive functions related to math talent differed from those related to math disabilities. Those with math talent were better at shifting attention with changing instructions than those with average math skills, and those with math disabilities had poorer visuospatial working memory skills than those with average math skills.…”
Section: Twice‐exceptionality and The School Psychologistmentioning
confidence: 99%